Rasio Investasi, Quick Ratio, Return on Investment, dan Pertumbuhan Perusahaan dalam Memengaruhi Dividend Payout Ratio (Studi Kasus pada 5 Perusahaan Industri Manufaktur di Bursa Efek Indonesia - Indrayenti INDRAYENTI (Jurnal Akuntansi dan Keuangan, 2010)
All companies have a goal of improving the welfare of the owners and investors.The company's goal can be achieved by maximizing the stock price, in order to improve the welfare of the shareholders of the company distributing dividends each year. Dividend policy of the company relating to the determination of the percentage of profits to be distributed to shareholders in the form of dividends or retained for future investment financing. Dividend policy has significant implications for investors and for companies, because it involves two parties and conflicting interests, namely the shareholders with dividends, and interest of the company retained earnings. The amount of profit is distributed as dividends declared a Dividend Payout Ratio (DPR). Dividend Payout Ratio is the ratio between the dividend with earnings per share expressed as a percentage.The problems that arise as a consequence of the divergence of interests between investors and companies to make the management company should be able to make the right policy on corporate dividend percentage by considering the factors that influence it. Therefore, researchers conduct research with the aim to determine the effect of variables investment ratio, quick ratio, return on investment, and firm growth partially and simultaneously the dividend payout ratio at 5 Industrial Manufacturing companies in the Indonesia Stock Exchange (formally Jakarta Stock Exchange) in the year 2003 to 2007. This research is expected to contribute to determine the effect of the investment ratio, quick ratio, return on investment, and growth of the company's dividend payout ratio which can then be used sabagai additional information in making investment decisions.The result showed that the individual test results show that of the four independent variables were examined, ie variable investment ratio, quick ratio, return on investment, and growth of the company, only the ratio of investment and growth in the company's effect on the dependent variable, the dividend payout ratio. While the test results simultaneously (together) shows the investment ratio, quick ratio, return on investment, and the growth of corporate influence the dividend payout ratio. Subsequent research suggested attention to other factors outside of the study were still associated with the dividend policy and also can use other companies listed on the JSE in addition to manufacturing companies. Observation period used can be extended so that more number of observations, it would be more valid to generalize the results of the study.